Use of seawater as the mix water for concrete - Bilici, Senem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
According to the United Nations World Water Development Report in 2018, the global demand for water has been increasing at a rate of about 1% per year over the past decades as a function of population growth and economic development, and it will continue to increase dramatically in the near future. In line with these estimates, researchers in many countries of the world focused on issues such as wastewater management and widespread use of seawater within the scope of sustainability. Since concrete is the most widely used building material in the world, construction sector is among the sectors that use signi cant amounts of water. Using seawater in the mixture as the mix water is potentially favorable from a sustainability viewpoint. However, the presence of high concentrations of chloride in the seawater can cause corrosion of steel reinforcement. This issue can be addressed by using non-corrosive synthetic structural bers. This thesis reports on the results of an experimental study to compare the fresh and hardened properties of tap water and seawater-mixed concretes. The experimental program included the following tests: (a) fresh concrete test (slump ow and density); (b) mechanical tests of hardened concrete (compressive strength test, modulus of elasticity test, three - point bending test and length change test); and (c) microstructural analyses of hardened concrete (SEM/EDAX observations and X-Ray Di raction analyses). No pronounced change was seen in mechanical performance of seawater concrete. Scanning electron microscopy and XRD analyses were used to better explain the experimental observations.
Keywords: Concrete -- Mixing.; Seawater -- Composition.